Elastic methyltrimethoxysilane based silica aerogels reinforced with polyvinylmethyldimethoxysilane. Issue 19 (9th April 2019) - Wang, Lukai; Feng, Junzong; Jiang, Yonggang; Li, Liangjun; Feng, Jian
Abstract : For designing more durable and stronger silica aerogels, elastic polyvinylmethyldimethoxysilane reinforced silica aerogels have been prepared successfully. Abstract : Native silica aerogels are fragile and brittle, which prevents their wider utility. For designing more durable and stronger silica aerogels, polyvinylmethyldimethoxysilane (PVMDMS) polymers as effective and multifunctional reinforcing agents were used to strengthen methyltrimethoxysilane based silica aerogels (MSAs). The PVMDMS polymer, which was composed of long-chain aliphatic hydrocarbons and organic side-chain methyl and alkoxysilane groups, was integrated into silica networks via a simple sol–gel process. Compared with MSAs, PVMDMS reinforced MSAs (PRMSAs) display many fascinating characteristics. PRMSAs exhibit improved hydrophobic properties (water contact angle of 136.9°) due to abundant methyl groups in the silica networks. Benefiting from the fine integration of PVMDMS polymers into MSAs, PRMSAs show a perfectly elastic recovery property, the compressive strength of which ranges from 0.19 to 1.98 MPa. More importantly, PVMDMS polymers have successfully suppressed the growth of secondary particles. Homogeneous silica networks formed by nanoscale particles give PRMSAs a high surface area of 1039 m 2 g −1 . Moreover, optimized PRMSAs also exhibit a low thermal conductivity of 0.0228 W m −1 K −1 under ambient conditions, and their thermal stability reaches up to 222.3 °C in air. All the results obtained from this paper will help us to design silica aerogels.